ANALISIS PUTUSAN HAKIM TENTANG WALI ADHAL DI PENGADILAN AGAMA WATANSOPPENG (STUDI TERHADAP PUTUSAN NO. 12/Pdt.P/2021/PA.Wsp) - Yul Hidayah; Muh. Jamal Jamil; Musyfikah Ilyas (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2022)
This study discusses the analysis of the Judge's Decision on guardian Adhal at the Watansoppeng Religious Court (Study of Decision No. 12/Pdt.P/2021/PA.Wsp). The sub-problem that the author raises is, how is the description of the case of the adhal guardian's application in the decision number 12/Pdt.P/2021/PA.Wsp, then the basis for the judge's consideration in determining the decision number 12/Pdt.P/2021/PA.Wsp. This type of research is field research which is then analyzed qualitatively using a juridical and syar'i approach, then this research is sourced from the results of direct interviews by the Religious Courts. The results of the study indicate that the determination to accept the applicant's application because the reason made by the guardian does not want to marry does not become a barrier to become a guardian. As for the judge's consideration in granting the petition regarding the guardian of Adhal because there are no grounds or elements that prevent the two parties from getting married, based on the evidence and testimony of the witnesses presented in the trial process, it was found that the reasons used by the guardian for not agreeing to become a guardian is proven to be inappropriate and contrary to syara', besides that the applicant and his prospective husband have been proven to be kafa'ah according to the applicable laws and regulations. The implication of this research is that marriage guardians are expected to reconsider more about rejecting the good intentions of someone to marry his brother, before carrying out the marriage, the prospective husband should introduce the family, namely the family of the woman and for the practitioners of Islamic law to socialize to the public regarding guardian adhal so that the community understands about this and there are no unwanted marriages.